NF-kappaB-inducing kinase is dispensable for activation of NF-kappaB in inflammatory settings but essential for lymphotoxin beta receptor activation of NF-kappaB in primary human fibroblasts. - Smith, C; Andreakos, E; Crawley, J; Brennan, F; Feldmann, M; Foxwell, B (2001)
The transcription factor NF-kappaB is of major importance in the biology of pro-inflammatory cytokines, such as TNF-alpha and IL-1alpha, and thereby is intimately involved in the process of inflammation. Understanding the mechanisms by which NF-kappaB is activated in response to inflammatory stimuli has become a major goal of inflammation research. The discovery of NF-kappaB-inducing kinase (NIK) as a TNFR-associated factor-interacting enzyme and a potential activator of the IkappaBalpha-kinase complex appeared to have identified an important element of the NF-kappaB activation pathway, a view that was supported by several subsequent studies. However, recent experiments in the alymphoplasia (aly/aly) mouse, which has missense point mutation (G885R) in NIK, has challenged that view. The reasons for the discrepancy between the different studies is unclear and could be due to multiple factors, such as cell type, species of cell, or primary vs transformed cell lines. One system that has not been investigated is primary human cells. Using an adenoviral vector encoding kinase-deficient NIK, we have investigated the role of NIK in LPS, IL-1, TNF-alpha, and lymphotoxin (LT) betaR signaling in primary human cells and TNF-alpha expression from rheumatoid tissue. These data show that, in the primary systems tested, NIK has a restricted role in LTbetaR signaling and is not required by the other stimuli tested. Also, there is no apparent role for NIK in the process of TNF-alpha production in human rheumatoid arthritis. These data also highlight the potential problems in extrapolating the function of signaling pathways between primary and transfected cell lines.